Investigation of graphene growth via molecular dynamics simulation. - Yoon , Tiem Leong (Universiti Sains Malaysia, 2016)
Molecular dynamics (MD) simulation with simulated annealing method is used to study the growth process of bi and tri-Iayered graphene on a 6H-SiC (0001) substrate. Tersoff-Albe-Erhart (TEA) potential is used to describe the interatomic interactions in the system. The growth mechanism, formation temperature, averaged carboncarbon bond length, pair correlation function, binding energy and the distance between the graphene and the SiC substrate are quantified.